Blocking Aδ- and C-fiber neural transmission by sub-kilohertz peripheral nerve stimulation - Zhang, Shaopeng; Chen, Longtu; Ladez, Sajjad Rigi; Seferge, Ahmet; Liu, Jia; Feng, Bin (Frontiers in Neuroscience, 2024)
We recently showed that sub-kilohertz electrical stimulation of the afferent somata in the dorsal root ganglia (DRG) reversibly blocks afferent transmission. Here, we further investigated whether similar conduction block can be achieved by stimulating the nerve trunk with electrical peripheral nerve stimulation (ePNS). We explored the mechanisms and parameters of conduction block by ePNS via ex vivo single-fiber recordings from two somatic (sciatic and saphenous) and one autonomic (vagal) nerves harvested from mice. Action potentials were evoked on one end of the nerve and recorded on the other end from teased nerve filaments, i.e., single-fiber recordings. ePNS was delivered in the middle of the nerve trunk using a glass suction electrode at frequencies of 5, 10, 50, 100, 500, and 1000 Hz. Suprathreshold ePNS reversibly blocks axonal neural transmission of both thinly myelinated Aδfiber axons and unmyelinated C-fiber axons. ePNS leads to a progressive decrease in conduction velocity (CV) until transmission blockage, suggesting activity-dependent conduction slowing. The blocking efficiency is dependent on the axonal conduction velocity, with Aδ-fibers efficiently blocked by 50-1000 Hz stimulation and C-fibers blocked by 10-50 Hz. The corresponding NEURON simulation of action potential transmission indicates that the disrupted transmembrane sodium and potassium concentration gradients underly the transmission block by the ePNS. The current study provides direct evidence of reversible Aδ-and C-fiber transmission blockage by low-frequency (<100 Hz) electrical stimulation of the nerve trunk, a previously overlooked mechanism that can be harnessed to enhance the therapeutic effect of ePNS in treating neurological disorders.